DaVinci Academie’s Travel Journey Visual Design - Angelina Patricia Handojo (Jurnal Desain Komunikasi Visual Nirmana, 2018)
DaVinci is an educational company that has two backing departments. One is aimed at children, namely DaVinci Publisher, and the other is for adults, namely DaVinci Academie. DaVinci Publisher is a department that offers education methods for children, and its vision is to develop kids with their educational products and materials about a way of thinking and learning. DaVinci Publisher has already gotten products to support children’s education from the design of the visuals and supporting media like textbooks, workbooks, binders, etc. However, DaVinci Academie still has nothing to support the education for adults and its target audiences who consist of directors, manager teachers, etc., and do not know about the messages that it carries. Finding the requirements to produce a suitable design of the visuals and the supporting media are needed to support the messages within a travel journey concept given by DaVinci Academie.